2021
DOI: 10.1101/2021.01.12.21249577
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intermediate-dose anticoagulation, aspirin, and in-hospital mortality in COVID-19: a propensity score-matched analysis

Abstract: BackgroundThrombotic complications occur at high rates in hospitalized patients with COVID-19, yet the impact of intensive antithrombotic therapy on mortality is uncertain.Research QuestionHow does in-hospital mortality compare with intermediate-versus prophylactic-dose anticoagulation, and separately with in-hospital aspirin versus no antiplatelet therapy, in treatment of COVID-19?Study Design and MethodsUsing data from 2785 hospitalized adult COVID-19 patients, we established two separate, nested cohorts of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
1
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 42 publications
4
60
1
6
Order By: Relevance
“…Other than anticoagulant therapy, antiplatelet therapy may also be a potential consideration for COVID-19. A propensity score-matched analysis reported a significantly lower incidence of in-hospital death in the aspirin cohort compared with no aspirin [114]. However, antiplatelet therapy will increase the risk of bleeding when combined with anticoagulant therapy.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Other than anticoagulant therapy, antiplatelet therapy may also be a potential consideration for COVID-19. A propensity score-matched analysis reported a significantly lower incidence of in-hospital death in the aspirin cohort compared with no aspirin [114]. However, antiplatelet therapy will increase the risk of bleeding when combined with anticoagulant therapy.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Several observational studies reported on the repurposing of established drugs like aspirin [35] and statins [36] to abolish COVID-19 clinical thrombo-embolic endpoints.…”
Section: Page 10 Proteomicsmentioning
confidence: 99%
“…Several observational studies reported on the repurposing of established drugs like aspirin [35] and statins [36] to abolish COVID‐19 clinical thrombo‐embolic endpoints. However, proteomic data are usually not available from these observational studies.…”
Section: Treatment Number Of Datasets (Subjects) Age (±Sd) Male/female Mean Cov50 Before Treatment (± Sd) Mean Cov50 After Treatment (± Smentioning
confidence: 99%
“…Unless formal anticoagulation is indicated, (per guidelines contingent upon D-Dimer levels), we recommend 1 baby aspirin daily (81 mg) for purposes of reducing clot and sludging via platelet inhibition (unless aspirin in the patient is contraindicated). [68][69][70][71][72][73][74][75][76][77]…”
Section: Baby Aspirinmentioning
confidence: 99%